STRATEGY DEVELOPMENT CHARACTER EDUCATION THROUGH EXTRACURRICULAR DANCE PROBATION IN SD BRAJAN KASIHAN BANTUL ACADEMIC YEAR 2015/2016 - Shinta Ayu Puspita Kumalasari; Sindhuredja, FX. Sindhuredja, FX. **) (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
Â ABSTRAKAbstract : This study aimed to the development strategy of character education in elementary Brajan Poor Bantul through extracurricular dance of the school year 2015/2016 , 152 student population , a sample class III , IV , and V, as well as an extracurricular dance teacher . Data collection technique; observation , interviews , documentation . The data is processed through the test requirements analysis , increase endurance, triangulation , reference material , were analyzed with the data collection , data reduction, a data display, and conclusion drawing. Strategy through the alignment of dance music and movement, gave a downbeat count, communicating the moral values synopsis of dance, as well as the interaction of teachers and students ; the role of teachers to develop character education as a facilitator , motivator , innovator ; barriers teacher of teachers themselves , facilities and infrastructure , students , and the environment.Â